Mesenteric Cyst in a Child with Abdominal Pain: A Perspective from Emergency Department Attendance - Sarah Mohammed Bin Hariz; Ahmed Hasan AlZaabi; Ghazy Habeeb Lutf; Biniam Tesfayohannes; Ayesha Musabbah Almemari (Eurasian Journal of Emergency Medicine, 2022)

(untitled)
Mesenteric cysts are rare benign intra-abdominal pediatric lesions. It has a variable clinical presentation from an asymptomatic mass to an acute abdomen that appears in the omentum or mesentery of the gastrointestinal tract. Abdominal ultrasound and complete surgical resection are the modality of choice for diagnosis and treatment. Here, we present 15 months old boy who presented to the emergency department with constipation and abdominal pain and was found to have a huge mesenteric cyst that was excised surgically.